Isotopic Composition of Gaseous Elemental Mercury in the Marine Boundary Layer of East China Sea. Issue 14 (20th July 2018) - Fu, Xuewu; Yang, Xu; Tan, Qingyou; Ming, Lili; Lin, Tian; Lin, Che‐Jen; Li, Xiangdong; Feng, Xinbin
Abstract: Characterizing the speciation and isotope signatures of atmospheric mercury (Hg) downwind of mainland China is critical to understanding the outflow of Hg emission and the contributing sources. In this study, we measured the concentrations of gaseous elemental mercury (GEM), particulate bound mercury, gaseous oxidized mercury, and the GEM isotopic composition in the marine boundary layer of East China Sea from October 2013 to January 2014. Mean (±1σ) GEM, particulate bound mercury, and gaseous oxidized mercury concentrations were 2.25 ± 1.03 ng/m 3, 26 ± 38 pg/m 3, and 8 ± 10 pg/m 3, respectively. Most events of elevated GEM are associated with the outflow of Hg emissions in mainland China. The 24‐ and 48‐hr integrated GEM samples showed large variations in both δ 202 Hg (−1.63‰ to 0.34‰) and Δ 199 Hg (−0.26‰ to −0.02‰). GEM δ 202 Hg and Δ 199 Hg were negatively and positively correlated to its atmospheric concentrations, respectively, suggesting a binary physical mixing of regional background GEM and Hg emissions in mainland China. Using a binary mixing model, highly negative δ 202 Hg (−1.79 ± 0.24‰, 1σ) and near‐zero Δ 199 Hg (0.02 ± 0.04‰, 1σ) signatures for China GEM emissions are predicted. Such isotopic signatures are significantly different from those found in North America and Europe and the background global/regional atmospheric GEM pool. It is likely that emissions from industrial and residential coal combustion (lacking conventional air pollutant control devices), cement and mercury production, biomass burning, and soil emissions contributed significantly to the estimated isotope signatures of GEM emissions in China. Key Points: Concentrations of speciated atmospheric mercury (Hg) including gaseous elemental mercury (GEM), particulate bound mercury (PBM), and gaseous oxidized mercury (GOM) and isotopic composition of GEM were measured in the marine boundary layer (MBL) of East China Sea (ECS) Outflow of Hg from mainland China is the dominant source of atmospheric GEM in the MBL of ECS and drive the GEM isotopic composition toward lower δ 202 Hg and higher Δ 199 Hg values Using a binary mixing model, highly negative δ 202 Hg (−1.79 ± 0.24‰, 1σ) and near‐zero Δ 199 Hg (0.02 ± 0.04‰, 1σ) signatures for China GEM emissions is predicted